2017
DOI: 10.1097/ico.0000000000001220
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Rebubbling for Graft Detachment After Descemet Membrane Endothelial Keratoplasty

Abstract: Rebubbling for DMEK graft detachment may result in similar visual outcomes as in uncomplicated DMEK, when performed within the first 6 to 8 postoperative weeks. However, rebubbled eyes may have lower ECD, which may be attributed to additional air bubble trauma and/or selection bias through more extensive manipulation during initial DMEK or higher risk of graft detachment in more complicated eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 30 publications
4
36
2
1
Order By: Relevance
“…Of note, all rebubblings performed in this study were performed within one month after DMEK. This is in accordance to a recent published study investigating the clinical outcome after rebubbling for graft detachment after DMEK in a series of 760 DMEK surgeries with forty-one eyes requiring rebubbling 25. The authors concluded that visual outcomes may be similar to uncomplicated DMEK when rebubbling is performed within the first six to eight weeks after surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Of note, all rebubblings performed in this study were performed within one month after DMEK. This is in accordance to a recent published study investigating the clinical outcome after rebubbling for graft detachment after DMEK in a series of 760 DMEK surgeries with forty-one eyes requiring rebubbling 25. The authors concluded that visual outcomes may be similar to uncomplicated DMEK when rebubbling is performed within the first six to eight weeks after surgery.…”
Section: Discussionsupporting
confidence: 90%
“…This may be the case by inconvenient recipient's properties like a shallow anterior chamber and the presence of vitreous pressure [6]. The endothelial cell loss of 35% after 6 months in our study was comparable to previous studies [16, 20, 21].…”
Section: Discussionsupporting
confidence: 86%
“…At the 6-month follow-up, only one eye required re-bubbling and none of the patients required repeated DMEK. Of note, our re-bubbling rate was very low compared to rates between 5.4% and 23% reported in other studies [16, 17].…”
Section: Discussioncontrasting
confidence: 80%
“…However, the time interval between DMEK and rebubbling seems to be of importance in the management of incomplete postoperative graft adherence. A series of 760 DMEK surgeries with 41 eyes requiring rebubbling (5.4%) investigating the clinical outcome after rebubbling for graft detachment after DMEK demonstrated that the visual outcomes may be similar to uncomplicated DMEK when rebubbling was performed within the first 6–8 weeks 15…”
Section: Discussionmentioning
confidence: 99%